2003
DOI: 10.1108/00012530310498888
|View full text |Cite
|
Sign up to set email alerts
|

Seeking alcohol information on the Internet

Abstract: It has been argued that people may be more willing to seek potentially threatening information on the Internet than they would in 'real life' (Joinson and Banyard, 2002). For alcohol drinkers, potentially threatening information includes diagnostic information on the amount they drink, and information about the negative effects of alcohol consumption. In the present study, participants with varying levels of alcohol intake and plans for change chose four alcohol-related articles to read (from twelve) using eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Past research has indicated that online environments serve as platforms to facilitate both information and social-emotional activities (Burnett, 2000;Liu and Larose, 2008). Indeed, the ability of online environments such as discussion forums and blogs to provide emotional and social support for their participants has been widely noted ( Joinson and Banyard, 2003;Coursaris and Liu, 2009). We uncovered two primary reasons for the reliance on online social support from our literature review.…”
Section: Related Workmentioning
confidence: 97%
See 1 more Smart Citation
“…Past research has indicated that online environments serve as platforms to facilitate both information and social-emotional activities (Burnett, 2000;Liu and Larose, 2008). Indeed, the ability of online environments such as discussion forums and blogs to provide emotional and social support for their participants has been widely noted ( Joinson and Banyard, 2003;Coursaris and Liu, 2009). We uncovered two primary reasons for the reliance on online social support from our literature review.…”
Section: Related Workmentioning
confidence: 97%
“…Indeed, the ability of online environments such as discussion forums and blogs to provide emotional and social support for their participants has been widely noted ( Joinson and Banyard, 2003;Coursaris and Liu, 2009). We uncovered two primary reasons for the reliance on online social support from our literature review.…”
Section: Introductionmentioning
confidence: 95%
“…Do at‐risk, self‐affirmed participants differ in how they search for and select material on the Internet, for example? The Internet contains information that both threatens and reassures, and there is evidence that people may be more naturally drawn to the latter (Dutta‐Bergman, 2004; Joinson & Banyard, 2003; Sillence, Briggs, Harris, & Fishwick, 2007); it would be reasonable to predict that self‐affirmation changes this in favour of more balanced data‐gathering, but this has yet to be tested.…”
Section: How Does Self‐affirming Reduce Resistance To Relevant Healthmentioning
confidence: 99%
“…This is particularly problematic in the eHealth context, where consumers can often find conflicting advice and are able to navigate to websites that tell them what they would prefer to hear. In one study, for example, a population struggling to modify their drinking behavior sought pro-drinking rather than anti-drinking material when left free to choose via the Internet [ 14 ]. In our own study, we are interested in the fact that Internet material often contains visual design elements, or cues, that are unrelated to the quality of the health information presented but that could be used to influence credibility judgments about the site and that may also subsequently influence acceptance and adherence to health advice.…”
Section: Introductionmentioning
confidence: 99%